Keterampilan Berbicara Bahasa Inggris Mahasiswa PNP dan Hubungannya dengan PBM Bahasa Inggris pada SMA dan SMK - Husna Maani; Baetty Baetty; Welsi Haslina (Politeknik Negeri Padang, 2015)
This study is a mixed methods case on English students in a Vocational Higher Education Institution (VHEI) in West Sumatera. It is aiming at investigating factors that influence English proficiency within this case study context by referrin g it to English teaching and learning experience in high schools. This research attempt was specified into measuring: (a) the differences and correlation between the students English learning process at both vocational high schools and high schools in general in West Sumatera and the English skills of VHEI students. The methods of data collection are students’ survey, unstructured interview with teachers, and observations at 5 high schools and 5 vocational high schools in 5 different regencies in West Sumatera. The findings reveal that only16.7% of the VHEI have the score ranged 50-75 on dan 83.23% students has very limited English speaking proficiency by the score 0-50.It is also found : (a) learning processes is similar to the learning situation at the VHEI and there is significant correlation between these two learning situation, (b) students’ achievement in other subjects do not differ from their English speaking skill and there is no significant correlation between these two variables,